Quality of life and wellbeing among HIV outpatients in East Africa: a multicentre observational study - Harding, Richard (BMC Infect Dis, 2014)
BACKGROUND: Global health investment has reduced HIV mortality and transmission. However, little is known of patient-reported outcomes alongside ART rollout. This study aimed to measure wellbeing using patient-reported outcome measures (PROMS) among outpatients at PEPFAR-funded facilities. METHODS: In a multicentre 2 country cross-sectional study, adults attending 12 facilities in Kenya and Uganda gave self-reported data on quality of life (physical and mental wellbeing dimensions), functional and a measure of multidimensional problems (physical, psychological, social and spiritual). RESULTS: Among the 1,337 participants, multidimensional problems were more common in psychological, spiritual and social domains than in physical. In multivariable analysis using GEE to adjust for facility effect, the mental health subscale of quality of life was lower for people with limited functional status (B = -5.27, 95% CI -5.99, 1. -4.56 p < 0.001) and higher for wealthier people (B = 0.91, 95% CI 0.48, 1.33, p < 0.001). The physical health subscale of quality of life was lower for those with limited functional status (B = -8.58, 95% CI -9.46 to -7.70, p < 0.001) and those who had a caregiver present (B = -1.97, 95% CI -3.72 to -0.23, p = 0.027), higher for wealthier people (B = 1.14, 95% CI 0.65, 1.64, p < 0.001), and positively associated with CD4 count (B = 1.61, 95% CI 1.08-2.14, p < 0.001). Multidimensional problems were more burdensome for people with limited functional status (B = -2.06, 95% CI -2.46 to -1.66, p < 0.001), and less burdensome with more education (B = 0.63, 95% CI 0.25-1.00, p = 0.001) or ART use (B = 0.94, 95% CI 0.34-1.53, p = 0.002). CONCLUSIONS: Multidimensional problems are highly prevalent, and worse with declining function. Importantly, ART use does not appear to be protective for self-reported physical and mental dimensions of quality of life. Assessment and management of self-reported wellbeing must form part of HIV care and treatment services to ensure maximum benefit from ART investment.